Strategies for combating bacterial biofilms: A focus on anti-biofilm agents and their mechanisms of action. Issue 1 (1st January 2018) - Roy, Ranita; Tiwari, Monalisa; Donelli, Gianfranco; Tiwari, Vishvanath
ABSTRACT: Biofilm refers to the complex, sessile communities of microbes found either attached to a surface or buried firmly in an extracellular matrix as aggregates. The biofilm matrix surrounding bacteria makes them tolerant to harsh conditions and resistant to antibacterial treatments. Moreover, the biofilms are responsible for causing a broad range of chronic diseases and due to the emergence of antibiotic resistance in bacteria it has really become difficult to treat them with efficacy. Furthermore, the antibiotics available till date are ineffective for treating these biofilm related infections due to their higher values of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC), which may result in in-vivo toxicity. Hence, it is critically important to design or screen anti-biofilm molecules that can effectively minimize and eradicate biofilm related infections. In the present article, we have highlighted the mechanism of biofilm formation with reference to different models and various methods used for biofilm detection. A major focus has been put on various anti-biofilm molecules discovered or tested till date which may include herbal active compounds, chelating agents, peptide antibiotics, lantibiotics and synthetic chemical compounds along with their structures, mechanism of action and their respective MICs, MBCs, minimum biofilm inhibitory concentrations (MBICs) as well as the half maximal inhibitory concentration (IC50 ) values available in the literature so far. Different mode of action of anti biofilm molecules addressed here are inhibition via interference in the quorum sensing pathways, adhesion mechanism, disruption of extracellular DNA, protein, lipopolysaccharides, exopolysaccharides and secondary messengers involved in various signaling pathways. From this study, we conclude that the molecules considered here might be used to treat biofilm-associated infections after significant structural modifications, thereby investigating its effective delivery in the host. It should also be ensured that minimum effective concentration of these molecules must be capable of eradicating biofilm infections with maximum potency without posing any adverse side effects on the host.